Strong piezoelectric response in layered CuInP2S6 nanosheets for piezoelectric nanogenerators. (August 2022) - Io, Weng Fu; Wong, Man-Chung; Pang, Sin-Yi; Zhao, Yuqian; Ding, Ran; Guo, Feng; Hao, Jianhua
Abstract: Piezoelectricity in two-dimensional (2D) materials have received particular attention because of their great potential in realizing nanoscale piezotronic devices. However, most 2D layered piezoelectric materials found so far possess only in-plane piezoelectricity and require the induction of stress by bending flexible substrate, which limits their integration with conventional rigid substrates such as silicon wafer. CuInP2 S6 is a promising 2D layered material that has attracted widespread devotion due to its diverse excellent properties including out-of-plane ferroelectricity and high stability at room-temperature. However, comprehensive investigation of piezoelectric effect in 2D CuInP2 S6 and its relevant piezoelectric device application is still at an initial stage compared to the extensive investigation of its ferroelectricity. Herein, we perform a quantitative analysis of the large out-of-plane piezoelectricity in multilayer CuInP2 S6 and therefore demonstrate the device application for 2D piezoelectric nanogenerator (PENG). Few-layer CuInP2 S6 nanosheet shows a high d 33 piezoelectric coefficient of 17.4 pm/V, outperforming other 2D layered piezoelectrics currently reported. Moreover, the PENG based on a single CuInP2 S6 nanoflake illustrates a maximum piezoelectric current and voltage responses of 1.7 nA and 12 mV, respectively. The experimental results are discussed based on the piezotronic effect. The strong piezoelectric response achieved in 2D CuInP2 S6 nanosheets warrants their potential to be adopted for future strain-modulable nanoelectronic and piezotronic devices integrated with silicon-based chips. Graphical Abstract: ga1 Highlights: A large d 33 piezoelectric coefficient of 17.4 pm/V is reported in few-layer CuInP2 S6 nanosheet investigated by PFM. 2D CuInP2 S6 -based piezotronic device is explored and its working principle is understood based on piezotronic effect. We firstly present a single 2D CuInP2 S6 nanosheet-based vertical piezoelectric nanogenerator integrated with silicon wafer.